Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/aps.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

G3BP2 is involved in isoproterenol-induced cardiac hypertrophy through activating the NF-κB signaling pathway

Abstract: The RasGAP SH3 domain-binding proteins (G3BPs) are a family of RNA-binding proteins that can co-ordinate signal transduction and post-transcriptional gene regulation. G3BPs have been shown to be involved in mediating a great diversity of cellular processes such as cell survival, growth, proliferation and apoptosis. But the potential roles of G3BPs in the pathogenesis and progression of cardiovascular diseases remain to be clarified. In the present study, we provide the first evidence that suggests the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The activation of β-AR regulates cardiac excitation–contraction and leads to the increase in heart rate and cardiomyocyte contractility [ 21–23 ]. The hyperactivation of β-AR results in cardiac hypertrophy, fibrosis, senescence, inflammation, and cardiomyocyte apoptosis and necrosis [ 24–29 ]. The treatment of NRCMs with ISO caused cardiomyocyte enlargement and increased the expression of ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of β-AR regulates cardiac excitation–contraction and leads to the increase in heart rate and cardiomyocyte contractility [ 21–23 ]. The hyperactivation of β-AR results in cardiac hypertrophy, fibrosis, senescence, inflammation, and cardiomyocyte apoptosis and necrosis [ 24–29 ]. The treatment of NRCMs with ISO caused cardiomyocyte enlargement and increased the expression of ANP and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that NF-κB activation is required for the progression of cardiac hypertrophy. Recently, Hong et al [ 24 ] reported that NF-κB inhibition with PDTC or p65 knockdown significantly decreased the hypertrophic responses. Moreover, IKK/NF-κB activation in cardiomyocytes caused significant inflammatory cardiomyopathy and heart failure, while inhibition of the NF-κB signaling pathway by a nondegradable IκBα decreased cardiac hypertrophy and dysfunction induced by Ang II stimuli and pressure overload [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the overexpression of G3BP1 alone is not enough to cause development of cardiac hypertrophy, it does have a role in the regulation of miR-1 during disease progression [67]. The potential role of G3BP2 in miRNA regulation in cardiac hypertrophy remains elusive, but it is involved in isoproterenolinduced cardiac hypertrophy by inducing the NFκB signalling pathway [68]. Interestingly, in situ hybridisation studies of G3BP2 mRNA in developing mouse embryos showed that its expression is reduced in the heart relative to other tissues (unpublished data by the author).…”
Section: G3bps and Micrornas (Mirnas)mentioning
confidence: 99%